Humanizing Digital Leadership: Coexistence of Empathy-AI from Women CEOs in HRM 5.0 - Kaur, Sukhmeet; Shukla, Manu (Journal of Emerging Management Studies, 2026)
Purpose - Human Resource 5.0 refers to the fifth generation of human resources, characterized by the realignment of HR processes and practices with technology, data, and analytics. This study examines the coexistence of Artificial Intelligence (AI) and empathy in women-led strategic leadership with reference to HRM 5.0. Design/methodology/approach - The study is grounded in an interpretivist, qualitative approach to analyze women CEOs on the Fortune 500 list. The secondary data were collected from publicly available sources, including interviews, posts, narratives, and company reports, associated with 55 women CEOs listed in Fortune’s 500 companies during 2024-2025. Open and axial coding techniques were used to identify themes in leadership and HRM 5.0. Findings - The study identifies three main leadership competency styles – empathetic (44%), servant (16%), and transformational (60%) that collectively define HRM 5.0. The women’s CEO strategically leveraged empathy practices alongside HRM 5.0 practices such as predictive analytics, digital learning, and people analytics to promote inclusivity, ethics, and psychological safety. Implications - The women CEOs demonstrate a unique ability to reinforce HRM 5.0 through AI-driven decision-making and humanistic values such as empathy, ethics, and inclusive engagement platforms. The study contributes to management literature by conceptualizing HRM 5.0 as a five-pillar model. Originality/value - The paper contributes to modern HRM literature by conceptualizing HRM 5.0 as a human-centric framework that centers human ethics, emotions, and behaviors within Artificial Intelligence, and by positing women CEOs as strategic enablers of empathetic AI-driven leadership.